Utilizing the Walking Interview to Explore Campus Climate for Students of Color. Issue 4 (1st October 2016) - Harris, Jessica
Abstract : This article explores the walking interview as a qualitative tool to assess campus climate. Using examples from a study that employed the walking interview, the author elucidates how this method of data collection allows for in situ understandings of participants' perceptions, spatial practices, biographies, social architecture, and social realms within the campus environment. The author also details how the walking interview may be useful in exploring the experiences of and empowering students of Color.